The Role of Crown Corporations in the Canadian Economy: An Analytical Framework - Edward M. Iacobucci; Michael J. Trebilcock (The School of Public Policy Publications, 2012)
Government interference in markets arouses heated emotions on both sides of the political spectrum. But the fact remains that governments of all stripes routinely play a direct role in the economy. Motivations run the gamut from the economic (correcting perceived market failures) to the ethical (addressing social injustice) to the nakedly political (ideology or the status quo demands it). This paper offers a highly readable theoretical and practical framework for understanding federal and provincial governments’ market interventions in sectors including power generation, alcohol and mail delivery. Public ownership can advance a range of normative objectives, so the choices, reasons and outcomes for the government, the Canadian economy, Crown corporation employees and the general public can vary as widely as the enterprises involved. But in asking why and how and assessing ways and means, the authors bring together a substantial body of knowledge and expertise, providing an essential guide to a phenomenon that, like it or not, will remain a major part of Canada’s economic landscape for a long time to come.